Comparison of jaw arch size in stunting patients at Asemrowo Public Health Center - Ida Bagus Narmada; Dyva Amalia Noor; Nafasya Putri Brillianti; Nurul Aisyah Rizki Putranti; Ananda Firman Putranto; Ratna Nurlia Alfiandini; Alida Alida (Indonesian Journal of Dental Medicine)
Background: The etiology of malocclusion is multifactorial; it can occur due to intrinsic, extrinsic factors, or a combination of both. Malnutrition, which is one of the extrinsic factors of malocclusion, is a frequent case in Indonesia. An example of a malnutrition case that commonly occurs in Indonesia is stunting in children’s growth and development, which can trigger malocclusions such as crowded teeth and bone crowding. Purpose: To identify the size of the dental arches in stunting sufferers at the Asemrowo public health center. Methods: In the study model of stunting patients, the length and width of the jaw arch were measured. The results of the measurements are then analyzed and compared with the data from the measurements of healthy children to see whether there are significant differences. Results: In terms of maxillary arch length, the 7-year-old age group yields p = 0.179. In terms of maxillary arch width, the 7-year age group yields p = 0.282. In terms of mandibular arch length, the 7-year-old age group yields p = 0.398. In terms of maxillary arch width, the 7-year age group yields p = 0.398. In terms of maxillary arch length, the 8-year age group yields p = 0.438. In terms of maxillary arch width, the 8-year-old age group yields p = 0.082. In terms of mandibular arch length, the 8-year-old age group yields p = 0.302. In terms of mandibular arch width, the 8-year-old age group yields p = 0.190. Conclusion: There is no significant difference between the length and width of the jaw arch in all age groups (p > 0.05).